Asymmetric photocurrent extraction in semitransparent laminated flexible organic solar cells - Bergqvist, Jonas; Österberg, Thomas; Melianas, Armantas; Aguirre, Luis Ever; Tang, Zheng; Cai, Wanzhu; Ma, Zaifei; Kemerink, Martijn; Gedefaw, Desta; Andersson, Mats R.; Inganäs, Olle (npj flexible electronics, 2018)
The manufacturing yield of the flexible organic solar cells is enhanced with a new lamination method by solving the shunting problem due to conductive inks. A collaborative team led by Olle Inganäs from Linköping University, Sweden fabricates polymer: PCBM all-organic solar cells in ambient conditions using the active layer as the lamination adhesive. The team shows that reduced exposure to ambient is critical to achieve high device efficiency and suppress degradation. The degraded devices generate asymmetric photocurrent due to the electron traps in the active layer. The reported active layer lamination method not only solves the shunting problem in a number of different polymer: PCBM combinations, but also provides wide tenability and control of the composition and vertical phase separation of the active layer.
Gesehen am 27.11.2019